Does the English Textbook for Young Learners in Indonesia Promote Gender Equality? - Dwi Titi Maesaroh; Yuni Utami Asih; Bibit Suhatmady (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
Education is a critical area in promoting gender equality to the young generation of this country. The curriculum that promotes gender equality could be represented in a textbook as a teaching material resource commonly used in Indonesia. This study is a critical discourse analysis that examines the gender representation in the English textbook for the third grade of primary school in order to discover whether or not the textbook promotes gender equality. The data were collected from “Grow With English” English book 3 published by Erlangga Publisher. The data in the forms of pictures, words, phrases, and sentences were then analyzed qualitatively by using Fairclough’s three dimensional frameworks and Halliday’s Systemic Functional Linguistics. The findings revealed that: the examined textbook represents genders equally in terms of the quantity in which females and males are portrayed equally in pictorial representation and names of characters. In terms of social roles of job positions, male and female are also portrayed occupying various professional occupations such as doctors, fire fighters, police officers, and so on. However, the portrayals of male and female in domestic roles and activities are still stereotypical in which females are portrayed doing more domestic activities and less active, while males are portrayed doing more active outdoor activities. These results may have the implication that the English teachers for young learners could improvise by providing more understanding about gender equality while using the textbook.